Hydroids (Cnidaria, Hydrozoa) collected on the continental shelf of Brazil during the Geomar X Oceanographic Operation - Grohmann, Priscila A.; Nogueira, Claudio C.; Da Silva, Vera Maria Abud P. (Zootaxa, 2003)
Hydroids (Cnidaria, Hydrozoa) collected on the continental shelf of Brazil during the GEOMAR X Oceanographic Operation. A total of 53 species of hydroids, belonging to 29 genera and 11 families, was collected at 57 oceanographic stations established during Operation GEOMAR X on board the Oceanographic Vessel “Almirante Câmara”, of the Ministry of the Navy, during May- June 1978. Areas investigated were the northern coast of the state of Rio de Janeiro, the coast of Espírito Santo, and the southern coast of Bahia. In the present contribution, the genus Antennella is recorded for the first time from the Brazilian coast. Antennella curvitheca Fraser, 1937 is reported for the first time from the southern hemisphere while Antennella campanulaformis (Mulder & Trebilcock, 1909) and Salacia desmoides (Torrey, 1902) are reported for the first time from the Atlantic Ocean. Five other species, Lafoea dumosa (Fleming, 1820), Antennella quadriaurita Ritchie, 1909, Nemertesia antennina (Linnaeus, 1758), Sertularella polyzonias (Linnaeus, 1758) and Hincksella cylindrica (Bale, 1888) were collected from Brazil for the first time. The reported bathymetric distributions of 28 species previously known from the Brazilian coast are extended. The known geographic distributions of seven species are extended along the coast, five northwards and two southwards.